1986
DOI: 10.1007/bf02429067
|View full text |Cite
|
Sign up to set email alerts
|

Plasma zinc levels in children with chronic diarrhoea

Abstract: We measured the plasma zinc concentration in a group of children with chronic diarrhoea. Fifteen patients with untreated coeliac disease had a mean plasma zinc level significantly lower than that of healthy children (69 micrograms/dl vs 96 micrograms/dl). In patients with chronic post-enteritic diarrhoea (n = 70) the mean plasma zinc level was in the normal range (100 micrograms/dl). The latter result suggests that our country a secondary zinc deficiency is not a feature of chronic post-enteritic diarrhoea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…34,35 Moreover, some subjects had suffered from moderate or severe attacks of acute diarrhea less than three weeks before the date of sample collection, which could have led to low serum zinc levels. [15][16][17] The cause of low serum zinc levels was investigated by comparing the anthropometric measurements of the concerned subjects to their calculated dietary intakes and a review of their medical history. In the youngest age group, 24 subjects with serum zinc of < 10.4 μmol/L had either very low levels (<75% of RDA for calories and <54% of RDA 36 for protein and other calculated nutrients), being dependent on breast milk mainly, with very little homemade mashed fruits, vegetables and rice (all low in zinc).…”
Section: Resultsmentioning
confidence: 99%
“…34,35 Moreover, some subjects had suffered from moderate or severe attacks of acute diarrhea less than three weeks before the date of sample collection, which could have led to low serum zinc levels. [15][16][17] The cause of low serum zinc levels was investigated by comparing the anthropometric measurements of the concerned subjects to their calculated dietary intakes and a review of their medical history. In the youngest age group, 24 subjects with serum zinc of < 10.4 μmol/L had either very low levels (<75% of RDA for calories and <54% of RDA 36 for protein and other calculated nutrients), being dependent on breast milk mainly, with very little homemade mashed fruits, vegetables and rice (all low in zinc).…”
Section: Resultsmentioning
confidence: 99%
“…It is generally assumed that a low plasma zinc concentration is indicative, in the majority of cases, of zinc deficiency. 7 In 1972, Hambidge et al 12 observed an association between poor growth and unsatisfactory zinc status assessed by low hair zinc levels. The same relationship was reported by Halsted et al in Iranian boys.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present study was to investigate prospectively the value of measuring plasma zinc levels in the diagnosis of CD in short‐statured children and to determine the sensitivity, specificity and positive and negative predictive values (PPV and NPV, respectively) of zinc for the diagnosis of monosymptomatic CD. Although a review of the literature revealed some reports of zinc deficiency in children with CD as consequence of intestinal malabsorption, 6–8 this seems to be a unique study on the levels of zinc in children with monosymptomatic CD who present with short stature.…”
mentioning
confidence: 95%
“…In contrast, zinc deficiency has been well documented in CD and a low serum zinc level is one evidence of multiple deficiencies in absorption in children with CD 11–13 , and zinc supplementation is recommended for mucosal recovery 14 .…”
mentioning
confidence: 99%
“…In contrast, zinc deficiency has been well documented in CD and a low serum zinc level is one evidence of multiple deficiencies in absorption in children with CD, [11][12][13] and zinc supplementation is recommended for mucosal recovery. 14 In this paper we evaluated basic antropometric, biochemical and hematological parameters as well as serum zinc levels in children with CD, presenting with chronic diarrhea and other common presentations such as anemia and short stature.…”
mentioning
confidence: 99%